Incident MCI and dementia in Hispanic and non‐Hispanic whites: Implications for ethnic comparisons of risk in Alzheimer's Disease Center data: Epidemiology: Dementia and risk in underrepresented populations. (7th December 2020) - Salazar, Hector; Norton, Derek L; Zuelsdorff, Megan; Wyman, Mary F; Carter, Fabu P; Benton, Susan Flowers; James, Taryn T; Johnson, Adrienne L; Lambrou, Nickolas H; Cordova, Susie Fernandez; Pinzon, Maria C Mora; Asthana, Sanjay; et al.
Abstract: Background: Recruitment strategies have different levels of success in reaching Hispanic populations, potentially introducing bias in large multicenter datasets, such as the National Alzheimer's Coordinating Center (NACC). The purpose of this study is to examine differences in incident mild cognitive impairment (MCI) and dementia between Hispanic and non‐Hispanic whites. Method: We included NACC data from 23, 963 participants with > 1 follow‐up visit. Additional inclusion criteria were: age 60+, did not have Downs syndrome, ethnicity Hispanic or non‐Hispanic, primary race as white, and cognitively normal or diagnosed with MCI at baseline. An event (i.e., conversion) was defined as the first visit/subject age when diagnosed with MCI or Dementia. To compare age‐of‐conversion between Hispanic and non‐Hispanic whites, we used Cox proportional hazard models with variable entry setup. Separate models were fit for baseline cognitive status (MCI vs. normal). Model covariates included sex; educational attainment; baseline diabetes, hypertension, and cardiac event status; referral source; family history of dementia; and primary etiology (for baseline MCI subgroup only). Unadjusted Kaplan‐Meier curves were calculated between Hispanic and White non‐Hispanic subjects for both baseline cognitive strata and outcome (conversion only vs. combined). Result: Normal cognition Hispanic participants exhibited significant elevated risk of conversion compared to White non‐Hispanic participants (HR=1.316, p=0.005), but risk was non‐significant for the composite event (HR=1.176, p=0.069). For baseline MCI participants, Hispanic ethnicity was significantly associated with reduced risk of both conversion and conversion/death (conversion HR=0.734, p=0.002; conversion/death HR=0.699, p<0.001). In all models, referral sources other than health professional were associated with reduced risk of event. Family history of dementia was associated with increased risk of conversion and conversion/death for those with normal baseline cognition (conversion HR=1.216, p<0.001; conversion/death HR=1.084, p=0.048), but not for those with baseline MCI. Conclusion: White participants with MCI, referred by clinicians exhibited greater likelihood of disease progression. These data suggest that Hispanic and non‐Hispanic whites in NACC may not be comparable. Therefore, caution should be exercised when interpreting analyses of data examining ethnic differences in incident MCI and dementia.